SCY-078 Demonstrates Significant Antifungal Activity in a Murine Model of Invasive Aspergillosis. (4th October 2017) - Borroto-Esoda, Katyna; Barat, Stephen; Angulo, David; Holden, Kirsty; Warn, Peter
Abstract: Background: Azoles are the most common anti-fungal agents for the treatment of Aspergillus infections. Echinocandins have demonstrated utility in Aspergillus infections, but are limited in use due to a lack of oral bioavailability. SCY-078 is a novel, oral and intravenous (IV), triterpenoid glucan synthase inhibitor with activity against Aspergillus and Candida, currently in clinical development for the treatment of invasive fungal infections. This study was conducted to evaluate the in vivo antifungal activity of SCY-078 in a murine model of invasive aspergillosis (IA). Methods: The in vivo activity of SCY-078 was assessed against a wild type (WT) and two azole-resistant A. fumigatus strains in neutropenic ICR mice. Five groups of mice (6/group) were infected IV into the lateral tail vein. Antifungal therapy was initiated 5 hours post infection and maintained for 7 days. SCY-078 was administered orally as a loading dose of 15/mg/kg or 20 mg/kg followed by BID maintenance doses of 7.5 or 10 mg/kg, respectively. Caspofungin (CSP) and amphotericin B (AMB) were administered QD by intraperitoneal injection (IP) at doses of 5 mg/kg and 10 mg/kg, respectively. The primary endpoint was survival at day 14, secondary endpoints were changes in fungal kidney burden and serum galactomannan index (GM). Pharmacokinetic analysis was conducted on blood samples at Day 7. Results: SCY-078 was well tolerated at all doses. Treatment with SCY-078 at 15 mg/kg/day and 20 mg/kg/day significantly increased mean survival in all strains (P ≤ 0.003). SCY-078 also resulted in significant reductions in fungal kidney burden ( P < 0.05) and serum GM levels ( P < 0.005) in all strains. Primary and secondary efficacy endpoints were also met in the groups treated with IP administration of CSP or AMB. Plasma levels of SCY-078 ranged from ≈15–20 μM*hr (AUC0-12 ) with Cmax ranging from ≈ 1–1.6 µg/mL for the two dose groups. Conclusion: SCY-078 demonstrated potent activity against WT and azole-resistant strains of A. fumigatus in a murine model of invasive aspergillosis. The exposure needed to achieve efficacy is in line with efficacious exposures reported in the invasive candidiasis models. These results support further development of SCY-078 as an oral treatment for IA infections. Disclosures: K. Borroto-Esoda, Scynexis Inc: Consultant, Consulting fee; S. Barat, Scynexis, Inc: Employee, Salary; D. Angulo, Scynexis, Inc: Employee, Salary; K. Holden, Evotec (UK) Ltd.: Employee, Salary; P. Warn, Evotec (UK) Ltd.: Employee, Salary